The Role of Emotional Regulation and Family Support on the Psychological Well-being of Working Mothers at PT XYZ - Samillah, Eriyanti; Nuradina, Kartika; Bernadus, Benny (Dinasti Research, 2026)
The study aims to determine working mothers at PT XYZ. The method used is a quantitative approach with multiple linear regression analysis. The t-test results partially indicate that family support has a positive and significant effect on psychological well-being (β = 0.702; p = 0.046 < 0.05), suggesting that higher levels of family support are associated with greater psychological well-being. In contrast, emotional regulation does not significantly influence psychological well-being (β = −0.402; p = 0.164 > 0.05), indicating that the respondent’s ability to regulate emotions does not directly improve psychological well-being among working mothers in this study. The F-test results indicate that emotional regulation and family support do not have a significant effect on psychological well-being (F = 2.989; p = 0.062). This implies that other elements are more pivotal in shaping psychological well-being, such as an individual’s capacity to control emotions, social support, life goals, mastery over their environment, autonomy, personal growth, and self-acceptance (Ryff, 1989).